2010
DOI: 10.2176/nmc.50.281
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Large Intrasylvian and Subpial Hematomas Caused by Rupture of Middle Cerebral Artery Aneurysm

Abstract: The clinical characteristics of intrasylvian and subpial hematomas caused by rupture of middle cerebral artery (MCA) aneurysm were examined in 86 patients admitted to our department with subarachnoid hemorrhage (SAH) caused by ruptured MCA aneurysms. A retrospective study of 26 patients with a large hematoma associated with SAH treated surgically within 48 hours evaluated clinical grade at admission, secondary development of cerebral swelling, ratio of hematoma removal, and incidence of symptomatic vasospasm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 10 publications
(11 reference statements)
0
14
0
Order By: Relevance
“…Lack of collateral circulation in MCA and tight adhesion between perforator vessels and clots contribute to the difficulty of complete evacuation of hematoma, and remnant hematoma constitutes the high rate of brain edema and symptomatic vasospasm most. Therefore, the outcome is comparatively poorer in this type of aneurysm than in others [2,6,7] . Strong attention is paid to this special type of aneurysmal intracranial cerebral hematoma (ICH) since Shimoda et al [8] first confirmed its etiology.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Lack of collateral circulation in MCA and tight adhesion between perforator vessels and clots contribute to the difficulty of complete evacuation of hematoma, and remnant hematoma constitutes the high rate of brain edema and symptomatic vasospasm most. Therefore, the outcome is comparatively poorer in this type of aneurysm than in others [2,6,7] . Strong attention is paid to this special type of aneurysmal intracranial cerebral hematoma (ICH) since Shimoda et al [8] first confirmed its etiology.…”
Section: Discussionmentioning
confidence: 75%
“…Intracranial hypertension and brain herniation are apt to happen in MCAAs patients associated with large SylH after aneurysm clipped, because of frequent postoperative vasospasm and severe secondary cerebral edema [7,18] . Thus, early prophylactic decompressive craniectomy would be useful to avoid this clinical dilemma.…”
Section: Prophylactic Hinged Craniectomy: An Effective Measure To Optmentioning
confidence: 99%
“…Removal of an ISH is technically more difficult than that of an ICH, due to involvement of fragile pial vessels. 18,24 In our cohort of patients with ISH, subpial hematoma expanded after uneventful surgery and required repeated craniotomy in 1 case, which may be a specific complication of the ISH group. Complications related to endovascular coiling exclusively occurred in the non-ISH group.…”
Section: Discussionmentioning
confidence: 83%
“…6 Indeed, Saito et al reported that delayed postoperative brain swelling (1 week after surgery) more likely developed in patients with SAH with ISH than in patients with SAH with intraparenchymal ICH. 18 Given less initial brain damage and associated secondary brain swelling, previous studies have aimed at intervening to treat one of these pathological processes by early hematoma evacuation or external decompression and have obtained reasonable outcomes from poor-grade SAH with ISH. 2,[19][20][21] Our results also supported validity of early decompression for treatment of SAH with ISH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation